2016
DOI: 10.1039/c6ra09897e
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of phenol using a new developed TiO2/graphene/heteropoly acid nanocomposite: synthesis, characterization and process optimization

Abstract: A heteropoly acid-modified TiO2/graphene nanocomposite can be introduced as a promising efficient visible driven photocatalyst to reclaim polluted water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Increasing the probability of photo-catalytic degradation of organic compounds by oxidants produced on the TiO 2 /CMK-3 surface was mentioned as the reason for the increased TOC removal. Rafiee et al also observed the same results in their study when they investigated the photo-catalytic degradation of phenol (39). It was observed that the TOC removal efficiency was less than the phenol degradation efficiency, which was related to intermediate products produced in the catalytic reaction.…”
Section: Mineralization Of Phenolsupporting
confidence: 53%
See 1 more Smart Citation
“…Increasing the probability of photo-catalytic degradation of organic compounds by oxidants produced on the TiO 2 /CMK-3 surface was mentioned as the reason for the increased TOC removal. Rafiee et al also observed the same results in their study when they investigated the photo-catalytic degradation of phenol (39). It was observed that the TOC removal efficiency was less than the phenol degradation efficiency, which was related to intermediate products produced in the catalytic reaction.…”
Section: Mineralization Of Phenolsupporting
confidence: 53%
“…In addition, as can be seen in Table 2, the degradation kinetics was investigated based on the first kinetic model (ln (C0 / C) = Kt) for different concentrations of the phenol. Considering this table, it is observed that kinetic constant rate decreases by increasing the initial concentration of phenol, which can be due to the probability of interaction between the phenol molecules and active radicals (39).…”
Section: Effect Of Initial Concentration Of Phenolmentioning
confidence: 92%
“…Phenolic compounds are among the possible pollutants that impact natural aquatic systems. They are used in agriculture and are present in many industrial processes, such as pulp and paper, synthesis of pharmaceuticals, oil refining, production of polymers and resins, and food processing [2,3,4,5]. As a result, phenols are now often found in wastewater and in natural water.…”
Section: Introductionmentioning
confidence: 99%
“…The US Environmental Protection Agency (USEPA), the National Pollutant Release Inventory (NPRI) of Canada and the European Union (EU) consider phenols and their derivatives as priority pollutants, due to their serious impact on humans, animals and the aquatic environment [2,4]. Therefore, wastewater treatment plants are requested to decrease the concentration of those compounds to the safety level, namely below 0.1–1.0 ppm [3,4]. Since phenols and phenolic compounds are chemically stable and highly soluble in water [3], phenols abatement is a challenge for the traditional wastewater treatment plants.…”
Section: Introductionmentioning
confidence: 99%
“…Phenol biodegrades slowly in the environment and is extremely toxic, teratogenic and refractory in nature, especially for highly concentrated phenol. 1 A number of technologies, including electrocatalysis, 2 photocatalytic degradation, 3,4 microwave and ultrasound methods, 5 catalytic ozonation, 6,7 and catalytic wet oxidation (CWO) 1, [8][9][10] have been developed for elimination of phenol. The methods of photocatalysis, ozonation and electrocatalysis are only suitable to eliminate wastewater with low-loaded organic compounds.…”
Section: Introductionmentioning
confidence: 99%